Wild ungulate use of underpasses: tunnel length and availability of crossing opportunity matters - Elfström, Marcus; Håkansson, Emma; Helldin, Jan Olof (Frontiers in Conservation Science, 2026)
Underpasses have a fundamental potential in mitigating infrastructure barriers for wildlife, considering that they are a relatively common feature across traffic networks. Increasing our understanding of the functionality of the different designs and localities of underpasses is therefore crucial within infrastructure planning and management. We analyzed crossing probability, based on movement-triggered automatic cameras, in moose (Alces alces) and roe deer (Capreolus capreolus), common wild ungulates in Scandinavia, in relation to underpasses with different designs and localities. We analyzed the design through passage width, height, and length, including different combinations of these size dimensions. We also categorized underpasses into three size levels considering all dimensions. We included the nearest distance to the alternative crossing site while controlling for season, group size, and whether wildlife visits occurred during daytime or nighttime. We compared 797 visits by moose across nine underpasses and 1,433 visits by roe deer across 13 underpasses. Increasing tunnel length lowered the crossing probability in both moose and roe deer. Tunnel length not exceeding 16.5 m had a crossing probability above 50% in moose, whereas tunnel length not exceeding 12.0 m had a crossing probability above 50% in roe deer. However, we found no correlation between crossing probability and passage width and height. Tunnel length may describe a perceived narrowness more efficiently than other size dimensions. In roe deer, crossing probability increased when alternative crossing sites were situated further away, whereas moose showed a tendency toward the same pattern. Nearest distances to alternative crossing sites farther away than 1,150 m were related to more than 50% probability of roe deer visits resulting in crossing through underpasses. Thus, we conclude that tunnel length (ranging from 7.0 to 39.0 m) and nearness to alternative sites to cross seem to be more important factors than other size dimensions among underpasses (with passage width ranging from 2.8 to 42.0 m and passage height ranging from 2.0 to 10.2 m) to explain crossing probability in wild ungulates. The impact on crossing probability from the availability of other crossing sites stresses the importance of securing crossing opportunities along infrastructure barriers at the home range scale of focal species.